Capture pumping technology - Welch, Kimo M.
This is a practical textbook written for use by engineers, scientists and technicians. It is not intended to be a rigorous scientific treatment of the subject material, as this would fill several volumes. Rather, it introduces the reader to the fundamentals of the subject material, and provides sufficient references for an in-depth study of the subject by the interested technologist. The author has a lifetime teaching credential in the California Community College System. Also, he has taught technical courses with the American Vacuum Society for about 35 years. Students attending many of these classes have backgrounds varying from high-school graduates to Ph.D.s in technical disciplines. This is an extremely difficult class profile to teach. This book still endeavors to reach this same audience. Basic algebra is required to master most of the material. But, the calculus is used in derivation of some of the equations. The author risks use of the first person I, instead of the author, and you instead of the reader. Both are thought to be in poor taste when writing for publication in the scientific community. However, I am writing this book for you because the subject is exciting, and I enjoy teaching you, perhaps, something new. The book is written more in the vein of a one-on-one discussion with you, rather than the author lecturing to the reader. There are anecdotes, and examples of some failures and successes I have had over the last forty-five years in vacuum related activities, I'll try not to understate either. Lastly, there are a few equations which if memorised will help you as a vacuum technician. There are less than a dozen equations and half that many rules of thumb to memorize, which will be drawn on time an again in designing, operating and trouble-shooting any vacuum system.